de.NBI Cloud federation through ELIXIR AAI - Belmann, Peter; Fischer, Björn; Krüger, Jan; Procházka, Michal; Rasche, Helena; Prinz, Manuel; Hanussek, Maximilian; Lang, Martin; Bartusch, Felix; Gläßle, Benjamin; Krüger, Jens; Pühler, Alfred; et al. (F1000Research, 2019)
The academic de.NBI Cloud offers compute resources for life science research in Germany. At the beginning of 2017, de.NBI Cloud started to implement a federated cloud consisting of five compute centers, with the aim of acting as one resource to their users. A federated cloud introduces multiple challenges, such as a central access and project management point, a unified account across all cloud sites and an interchangeable project setup across the federation. In order to implement the federation concept, de.NBI Cloud integrated with the ELIXIR authentication and authorization infrastructure system (ELIXIR AAI) and in particular Perun, the identity and access management system of ELIXIR. The integration solves the mentioned challenges and represents a backbone, connecting five compute centers which are based on OpenStack and a web portal for accessing the federation.This article explains the steps taken and software components implemented for setting up a federated cloud based on the collaboration between de.NBI Cloud and ELIXIR AAI. Furthermore, the setup and components that are described are generic and can therefore be used for other upcoming or existing federated OpenStack clouds in Europe.
Keywords: Software; Německo; Authentication; software; de.NBI; biologické vědy; ELIXIR; Life Sciences; Authorization; Biological Science Disciplines; OpenID Connect; Germany; de.NBI Cloud; Cloud Computing